Management of multiple primary prostate malignant tumors: case report of synchronous prostatic adenocarcinoma and lymphoma - Zhuang, Weihuang; Wu, Huiqiang; Cai, Zhiyin; Cai, Nina; Liu, Weihui; Liu, Wanyi (Frontiers in Oncology, 2025)
The occurrence of multiple primary prostate malignant tumors is extremely rare and there is no consensus on its diagnosis and treatment. This article presents an elderly male patient with both acinar adenocarcinoma of the prostate and small lymphocytic lymphoma (SLL) invading the prostate. He was treated with ibrutinib for the lymphoma and goserelin and bicalutamide for the prostate cancer, resulting in control of both conditions. This case highlights the complexity of diagnosing and managing multiple synchronous prostate malignancies. TP53 mutation may play a central role in dual clonal evolution. Multidisciplinary collaboration and individualized treatment plans are essential in managing rare presentations of prostate MPMT.